Welcome to Westonci.ca, where you can find answers to all your questions from a community of experienced professionals. Ask your questions and receive detailed answers from professionals with extensive experience in various fields. Explore comprehensive solutions to your questions from a wide range of professionals on our user-friendly platform.

1/3 (6y - 9) = -2y + 13 what is the answer?

Sagot :

Answer:

4

Step-by-step explanation:

1/3(6y-9)=-2y+13

6/3y-9/3=-2y+13

2y-3=-2y+13

2y-(-2y)-3=13

2y+2y-3=13

4y-3=13

4y=13+3

4y=16

y=16/4

y=4